The Impact of International Marketing Strategies on Export Performance - Reza Rezaee (کاوش‌های مدیریت بازرگانی, 2017)
Selecting an input method is one of the most critical and important strategic decisions for companies that seek to expand globally and have chosen their target markets. The aim of this study is to investigate the impact of international marketing strategies on the export performance of manufacturing and export companies. This study is objective-based and functional. Also, according to the way of the data are collected, it is a descriptive and correlational study. The statistical population of this study comprised the manufacturing and export companies of West Azarbaijan. The data were collected in the second half of 2014 using a standardized questionnaire, and interviews as a complementary tool. To assess the reliability of the questionnaire, Cronbach’s alpha coefficient was used. To analyze the data, Kolmogorov-Smirnov test and a regression software package of SPSS21 were used. The analysis of data showed that international marketing strategies have a significant impact on export performance. The sub-hypothesis suggested that full standardization strategies have no significant effect on it, fully adaptive strategies have a significant effect and fairly adaptive strategies hasn’t significant effect on export performance.